Hawkes Processes: A Modeling of the Offer Book in the Brazilian Stock Market - Sampaio Maluf, Yuri (2017)
This paper discusses the Hawkes process to modeling of the offering book, especially the ETF it iShare Ibovespa index fund. The study aimed to investigate the dynamics of the influences of the offers in relation to the past orders. We study too to the interaction of the order rates of the opposing sides of the Book. Another point addressed is the verification of the operating strategy that captures the dynamics studied. At the first moment, the univariate approach was performed and in the second moment the multivariate of the Hawkes process. The results show that in both cases the Hawkes process it fits well to the data. The fit model indicates that agents have similar behaviors when they act as buyers or sellers of assets. As for the strategy, it was not possible to establish spare gains from changes in bid rates. However, these results are due to the it bid-ask spread more that the predictive capacity of the functions.